Effectiveness of the Conservative Surgical Management of the Ameloblastomas: A Cross-Sectional Study - Rocha, André Caroli; Fonseca, Felipe Paiva; Santos-Silva, Alan Roger; Lourenço, Silvia Vanessa; Ceccheti, Marcelo Minharro; Júnior, Jayro Guimarães (Frontiers in Oral Health, 2021)
Ameloblastoma is a benign, but locally aggressive odontogenic neoplasm, whose appropriate therapeutic management remains highly debatable. The aim of this study was to evaluate the reliability and effectiveness of the two conservative surgical therapeutic protocols (curettage with peripheral ostectomy only and curettage plus cryotherapy) for the management of ameloblastomas. About 53 cases of the ameloblastomas treated in 9 years were retrospectively analyzed regarding their clinical, histopathologic, radiographic, and therapeutic data. The results and the postoperative complications related to both the therapeutic protocols were also statistically investigated. A slight female preponderance was seen (1.12:1.0) with a mean age of 27.1 years. The posterior mandible was the most affected site and dental involvement was frequently found. Multilocular lesions causing the alterations of the bone cortices were the most common radiographic findings. Recurrences were seen in 9.4% of the cases and although the patients submitted to curettage plus cryotherapy have shown an increased incidence of wound dehiscence, infection, and paresthesia, only bone sequestration proved to be significantly more frequent in this group compared to the patients treated by curettage with peripheral ostectomy only. The incidence of the recurrences following the conservative management is low and cryotherapy use as an adjuvant tool must be rationally considered.